Soroprevalência de hepatite C em pacientes em hemodiálise no Estado de Minas Gerais - Joao Milton Martins Oliveira Penido (2006)
Introduction: Hepatitis C is a worldwide public health problem. Patients with chronic renal failure (CRF) in hemodialysis (HD) programs comprise a risk group for acquisition of hepatitis C virus (HCV) infection. HCV seroprevalence in patients on HD has fallen in recent years as a result of public health policies adopted in developed and developing countries.However, prevalence in this group still remains higher than in the general population. The seroprevalence of HCV in patients on HD varies according to the serological screening test used, and geographical variations in seroprevalence have been detected in countries of theAmericas, Europe and Asia. The main risk factors for patients on HD acquiring HCV are: previous history and number of blood transfusions, duration of CRF and time on HD and seroprevalence of HCV in the HD healthcare unit. The risk of HCV transmission by transfusion of blood derivatives in patients on HD fell dramatically in various countries, as aresult of the introduction of screening tests in blood banks and HD units and the administration of erythropoietin for the treatment of anemia. The majority of publications have emphasized nosocomial transmission of HCV in HD units. Various factors may affect the risk of nosocomial HCV transmission to patients on HD, including: sharing items amongpatients, physical proximity to an infected patient, contamination of HD equipment, rupture of dialyzer membranes and inappropriate reuse of dialyzers. Violation of universal measures for the control and prevention of infections has been shown to be one of the main causes of nosocomial transmission. The seroprevalence of HCV in health professionals is three-fold that of workers in other professions. Seroprevalence ranging from 0-10% has been reported among staff working in HD units.Objectives: The objectives of this study were to evaluate the seroprevalence of HCV in patients submitted to HD; to correlate this seroprevalence with the time of treatment on HD; to investigate the anti-HCV seropositivity in health professionals, the date of theirseroconversion and duration of their employment in HD units; to investigate the existence of a correlation between mean HCV seroprevalence and the municipal and regional human development index (HDI); and to describe the demographic data, structure and level oforganization of the healthcare units. Methods: In this study, patients from 66 healthcare units in 13 geographical regions of the Brazilian state of Minas Gerais were studied using a validated questionnaire and considering the positive values of anti-HCV (Elisa III) tests, performed in these units between January and December 2003. Results: The majority of patients were male (56.2%), between 41 and 60 years old. The maincauses of CRF were arterial hypertension (30%), chronic glomerulonephritis (24%) and diabetic nephropathy (20%). The mean seroprevalence of HCV in the 66 healthcare units of the state of Minas Gerais was 13 ± 9.5% and the three-monthly seroprevalence was below20%, 15% and 10% in 75%, 50% and 40% of the healthcare units, respectively. When the healthcare units were grouped according to HCV seroprevalence into low (< 5%), medium (5- 15%) and high seroprevalence (> 15%), 20% of the units were found to have lowseroprevalence, 42% medium and 37.5% were found to have high seroprevalence. No correlation was found between municipal HDI and HCV seroprevalence (r=0.059; p=0.70), or between regional HDI and mean HCV seroprevalence (r=0.42; p=0.174). However, in theregions in which the HDI was higher, HCV seroprevalence was also higher. Mean monthly HCV seroprevalence in the 12 healthcare units in the city of Belo Horizonte was 12%, being the minimum annual mean 3.0% and the maximum 22.4%. There was a positive correlationbetween HCV seroprevalence and time on HD, in patients on HD in Belo Horizonte (p<0.05). The seroprevalence of anti-HCV seropositivity was investigated in 387 healthcare professionals, (29%) working in 14 healthcare units (19%) in the state of Minas Gerais. The mean number of professionals in each healthcare unit was 27 (7%) and these were divided into two groups, according to their time of professional activity: <10 years (G1) and > 10 years (G2). In G1, there were no cases of anti-HCV seropositivity. In G2, three members of staff were anti-HCV seropositive, one of whom referred having had an accident withcontaminated material. The mean time of work of the seropositive staff in the healthcare units was 15.6 years. The seroprevalence of anti-HCV seropositivity was 0.8% when all the healthcare professionals were taken into consideration and 1.3% when only G2 was considered. Between the staff members in G2, anti-HCV seropositivity was not related to thetransfusion of blood derivatives, tattoos, piercing or the use of injectable drugs. There was no statistically significant difference considering HCV seroprevalence between G1 and G2 when it came to the time of occupational exposure (p=0.27). The structure and level of organizationof the great majority of the healthcare units in the state of Minas Gerais is in accordance with the guidelines defined in the Ministry of Healths Directive 2042, dated October 12, 1996. Conclusions: In conclusion, the seroprevalence of HCV in patients on HD in the state of Minas Gerais is 13 ± 9.5% and is higher than that of the general population, but has beenfalling in recent years; seroprevalence of HCV in patients with CRF on HD in the state of Minas Gerais is similar to rates described in some european countries and in the United States; variability in the seroprevalence of HCV was found among healthcare units in thesame municipality and among healthcare units of different regions of the state of Minas Gerais; the calculation of anti-HCV seroprevalence in the majority of healthcare units was hindered by the presence of old cases of hepatitis C; no increase was observed in the frequency of HCV seroprevalence in the healthcare units during the study; a statisticallysignificant correlation was found between HCV seroprevalence and time of treatment on HD; there was no statistically significant correlation between municipal and regional HDI and seroprevalence of HCV in the healthcare units evaluated; HCV seroprevalence in the healthprofessionals studied is similar to that described in the literature; the majority of the healthcare units in the state of Minas Gerais are structured according to the guidelines of Directive 2048; nosocomial transmission of hepatitis C in the healthcare units should be prevented through the rigorous adoption of universal measures for the control of infections,that are fundamental for validation and strategic planning of preventive methods.